2021
DOI: 10.55843/ivisum2116065v
|View full text |Cite
|
Sign up to set email alerts
|

Quality Costs Concept and Measurement –Does a Reaffirmation in a New Direction Needed?

Abstract: This study primarily aims at presenting a realistic picture of the utilitarian nature of quality costs in companies around the world. This has led to researching the quality costs applications levels, the percentage share of the total quality costs, the percentage share measuring the quality costs categories, as well as the measured percentage shares of the quality costs in the companies. The analytical research methodology relies on an integrated chronological, comparative, logical and systematic analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to Velkoska & Tomov [22] quality costs should not be underestimated, that is corroborated by the fact that they contribute significantly to the total product creation costs that can reach up to 40%, or 38% of the company sales value or 33% of the value of the sales contracts. The same study presented an overview of published research studies about the extent to which companies apply quality costs, which quality costs categories do usually measure, as well as the quality costs measured values.…”
Section: Literature Reviewmentioning
confidence: 95%
“…According to Velkoska & Tomov [22] quality costs should not be underestimated, that is corroborated by the fact that they contribute significantly to the total product creation costs that can reach up to 40%, or 38% of the company sales value or 33% of the value of the sales contracts. The same study presented an overview of published research studies about the extent to which companies apply quality costs, which quality costs categories do usually measure, as well as the quality costs measured values.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The empirical studies of Ayach et al (2019), Prickett and Rapley (2001), Rabfeld et al (2015) and Satanov a et al (2015) showed that most of the companies do monitor internal and external failure costs, while the study of Biadacz (2021) showed that companies monitor appraisal costs. A more detailed analysis related to this issue, as well as the measured values of the quality costs categories can be found in the study of Velkoska and Tomov (2021).…”
Section: Categories Of Quality Costsmentioning
confidence: 99%